Conceptual framework for the formulation of strategies to support registered nurses in their utilisation of the nursing process when executing their roles and functions in local-level Primary health care (PHC) practicein Namibia - Iita, Hermine; Iipinge, Scholastika; Van Dyk, Agnes (International Journal of Health, 2016)
This paper describes the conceptual framework upon which the development of strategies to support use of the nursing process by registered nurses in local-level Primary health care practice in Namibia was based. The conceptual framework was developed based on the findings of phase 1 of this study, which was a situational analysis to explore and describe the use of the Nursing Process by registered nurses in local level primary health care practice in Namibia and to identify constraints that registered nurses in local level Primary health care practice face as they implement the nursing process in their daily practice. The study was conducted in four phases namely as follow: Phase1: Needs assessment quantitative survey; Phase 2: Conceptualisation of findings from phase 1; Phase 3: Development of strategies to support the roles and functions of the registered nurse in local level PHC and Phase 4: Validation of these strategies. This article focusses on Phase 2: Conceptualisation of findings from phase 1 and it describes objectives 4 of the study namely, to develop a conceptual framework on which to base the formulation of relevant strategies.From phase 1 which focused on needs assessment, findings indicate that registered nurses in local level Primary health care practice in Namibia fulfill most of their expected role functions. However, five main problem areas were identified. The challenges identified were categorised according to the five elements of PHC and management, namely, water and sanitation and related environmental health issues; nutrition and food supply; health education and communication; community diagnosis and care; and management support or administration, including research.It was concluded that strategies needed to be developed to support registered nurses in their daily local Primary health care practice.The development of the conceptual framework, which guided the development of strategies to support registered nurses use the nursing process in local level Primary health care practice, makes this study an original contribution to the body on knowledge.